2009
DOI: 10.1097/prs.0b013e3181a075ea
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Plastic Surgery Residency Applicant Survey: Characteristics of Successful Applicants and Feedback about the Interview Process

Abstract: Integrated plastic surgery residency training is highly competitive, with the number of interview invitations correlating with academic performance and, to a lesser extent, research. Applicant feedback from this survey can be used to improve the application and interview process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 3 publications
2
71
0
Order By: Relevance
“…It is also an opportunity for plastic surgery programs to learn more about the applicant during an away rotation. 11 Despite the rationale for completing a visiting away rotation, we found that only 29 percent of applicants matched at a program at which they completed an away rotation. This is in line with previous reports: a 2010 study found a match rate of 29 percent, and one study from 2012 found a 26 percent match rate.…”
Section: Our United States Medical Licensing Applicationmentioning
confidence: 86%
“…It is also an opportunity for plastic surgery programs to learn more about the applicant during an away rotation. 11 Despite the rationale for completing a visiting away rotation, we found that only 29 percent of applicants matched at a program at which they completed an away rotation. This is in line with previous reports: a 2010 study found a match rate of 29 percent, and one study from 2012 found a 26 percent match rate.…”
Section: Our United States Medical Licensing Applicationmentioning
confidence: 86%
“…Despite the advantages of an independent path of admission to plastic surgery, the integrated path is gradually becoming the mainstream method of training across Canada and the United States. To that end, we, as plastic surgery educators, must encourage interested applicants to obtain as much elective experience as possible to both assist students in their career choice and selection committees in identifying capable applicants (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Applicants with ≥1 peerreviewed publication(s) received a statistically significant greater number of interviews compared with applicants with no research publications (6). An applicant's quality of responses to interview questions was listed within the top five personal traits by program directors (Table 3) (3,8,9).…”
mentioning
confidence: 99%